Risk and Real Estate Investment Trust (REITs) Return: Evidence from Listed Public Trust - Mohamad, Nor Edi Azhar Binti; Saad, Noriza Mohd; Bakar, Suzaida (The Indonesian Capital Market Review, 2011)
This study examines an association of risk and returns of REITs from Malaysian REITs listed companies. The secondary data for analysis is retrieved from Bloomberg's Database of all 13 listed REITs in the Bursa Malaysia main market for three year period, from 2007 to 2009 with quarterly observation. The dependent variables are average return, expected return using Capital Asset Pricing Model, Sharpe Index, and Jensen Alpha Index. The independent variables represented by standard deviation, beta, trading volume, gross domestic product, inlation rate, and share price. The control variable for this study is type of REITs, whether it was categorized as Islamic or conventional REITs. Applying correlations and multiple regression analysis, the results provide evidence on the association between return and risk on REITs. This study is also hoped to bring beneits to the public listed company and shareholders in obtaining the key factors in determining the REITs yield.